Risk behavior for obesity: a conceptual analysis according to Walker and Avant - Vinícius Rodrigues de Oliveira; Amanda Soares; Allyne Fortes Vitor; Maria Isabel da Conceição Dias Fernandes; Francisca Marta de Lima Costa Souza; Jonas Sâmi Albuquerque de Oliveira (Revista Brasileira de Enfermagem, 2025)
ABSTRACT Objective: To analyze the concept of risk behavior for obesity using the Walker and Avant method. Methods: A theoretical study employing conceptual analysis, operationalized through a scoping review. Searches were conducted in the following data sources: BVS, MEDLINE, Embase, and Scopus. Studies available in full text were included, while duplicates and those not aligned with the review’s theme were excluded. Results: The conceptual analysis was based on 16 articles, which highlighted the most prevalent use of the concept in the fields of public health and nutrition. Twelve defining attributes related to diet, physical activity, and general habits were identified. Among the antecedents and consequences, the most notable were gender and age group as antecedents, and increased susceptibility to overweight/obesity as a consequence. Final Considerations: The analysis contributed to clarifying the concept of risk behavior for obesity. It is recommended to apply this concept in Nursing practice.